Perancangan Mesin Potong Torch Asetilen Dengan Gerak 2Axis Menggunakan Sistem Kontrol Arduino - Alfian Alfian (Politeknik Negeri Padang, 2023)
The problem of the oxy-acetylene welding plate cutting tool that is commonly used today is still in a manual way, and is not equipped with driving equipment. This results in the performance of the oxy-acetylene welding plate cutting tool when cutting is not optimal and efforts need to be made to improve the cutting tool in order to facilitate work. The purpose of this research is to produce a construction design of an automatic oxy-acetylene welding plate cutting tool. and can determine the suitability of mechanical components with the arduino control system used. The working method of the tool design process includes work preparation, data collection and making the formulation of problems and objectives to be achieved. Literature study by looking for articles, which are updated to produce solutions to existing problems. Making component and assembly designs and simulations by making calculations and uses on the mechanical construction and control systems used. Using the application of the ZW3D licensed computer aid design program, this research created a design for oxy-acetylene welding plate cutting tools by combining oxy-acetylene welding with stepper motors driven by Arduino control. Producing automatic motion with x and y axes, so that it can facilitate cutting work. The size of the designed tool is 700 mm x 700 mm x 800 mm. From the calculation, the maximum torque required by the plasma cutting table is 0.218 Nm, and the maximum power is 6.845 Watt. The motor chosen is a Nema23 stepper motor because the price is relatively cheap and in accordance with the calculation specifications. Lead Screw is used as a converter of rotary motion from stepper motor into linear motion, with specifications used with diameter = 8 mm, length = 500 mm and pitch = 2 mm.